L’auteur et l’histoire : l’éloge d’Athènes dans le Ménexène de Platon et le Panathénaïque d’Isocrate - Claudia Brunello (Cahiers des Études Anciennes, 2023)
In both Menexenus and Panathenaicus the narrative frame includes a dialogue between a master and one of his disciples. In both cases, this narrative device allows the author to comment on his own speech. Nevertheless, these two texts appear to be very enigmatic in the eyes of the reader, who wonders about the real thoughts of Plato and Isocrates while examining the characters’ statements celebrating the Athenian glories. By analyzing the historical exempla, the essay aims to investigate the author’s role in re-elaborating the rhetorical tradition and transmitting memory, thus scrutinizing the possibilities and the limits of rhetoric in relating the past.